Sosialisasi Hasil Penelitian Nanomaterial sebagai Demulsifier pada Emulsi O/W Sumur-X di PT. SPR Langgak: Research Exposure of Nanomaterials as a Demulsifier in Well-X O/W Emulsion at PT. SPR Langgak - Umar, Mursyidah; Sapitri, Sapitri; Rita, Novia; Putri, Rizka Haswinda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The problem of oil-in-water (O/W) emulsions is still a concern for the oil and gas industry. This is because the emulsion will have an impact on the scale in the flowline, production line, and gathering station and corrosion in the pipeline and will also hurt the environment. Therefore, the PKM TEAM, Faculty of Engineering, and Islamic University of Riau held service activities at PT. SPR Langgak to disseminate research results regarding the use of new materials in the form of nano-graphene oxide (GO) materials as demulsifiers for O/W emulsions. In this socialization, data on the volume of oil that has been separated from the water will be presented, and how much residual oil concentration is in the separated water content will also be socialized. Then, it will be stated that nano-GO can reduce turbidity, TDS, and salinity of water separated from oil compared to the standards set by the Minister of Environment Regulation. It is hoped that this activity will increase the knowledge of the oil industry in the development of new types of demulsifier materials today.